Penyuluhan Pijat Common Cold dalam Mengatasi Batuk Pilek Balita untuk Meningkatkan Pengetahuan Ibu di RW 8 Tulusrejo - Elmita Maesarah; Sri Sunaringsih Ika Wardojo; Bonita Suharto (Lembaga Pengembangan Kinerja Dosen, 2024)
Acute Respiratory Tract Infection (ARI) is an infectious disease that attacks the upper respiratory tract and lower respiratory tract which can be caused by the entry of bacteria and viruses into the respiratory tract which lasts for 14 days. This counseling aims to improve mother’s knowledge and handling of coughs and colds in toddlers. The method used is to provide materials and practices as well as a questionnaire session to mothers of toddlers who attend the RW 8 Tulusrejo integrated health service post. After the counseling, the results obtained were that mothers knew how to handle coughs and colds in toddlers by doing common cold massage.